Effects of School Closures Resulting From COVID-19 in Autistic and Neurotypical Children - Genova, Helen M.; Arora, Aditi; Botticello, Amanda L. (Frontiers in Education, 2021)
The purpose of this study was to assess differences in negative consequences resulting from pandemic-related school closures between autistic and neurotypical children. We predicted that more negative consequences overall would be reported for children with autism compared to neurotypical children. We also expected to observe differences in the types of stressors reported between these two groups, with disruptions to daily routines more commonly reported for children with autism and stress due to social isolation more commonly reported for neurotypical children. Participants were parents of school-aged children, ages of 4-15 years old, who responded to an online survey (N=250). Parental perspectives were collected using the Covid-19 Adolescent Symptom and Psychological Experience Questionnaire (CASPE). Parents in the autism group were additionally asked to respond to a survey about autism-specific stressors which may have increased during the pandemic, such as behavioral concerns, therapy disruptions, and hygiene issues. The majority of the respondents (65%) were parents of children with autism and 35% were parents of neurotypical children. Parents of autistic children were more likely to report that their child was negatively affected by routine changes, whereas parents of neurotypical children were more likely to report that their child was affected by social isolation. Overall, parents of children with autism were more than three times as likely to report negative changes in their child compared to parents of neurotypical children. When asked about autism-specific stressors, parents of autistic children reported concerns related to hygiene, behavioral regression, therapy disruption, meltdowns, and returning to school. The effects of the COVID-19 pandemic and prolonged school closures have disrupted the lives of children. Our results indicate that children with autism are at greater risk for negative outcomes due to emergency-related school disruptions. These findings have implications for educational planning for this vulnerable population for future public health crises.